Generasi Hebat Tanpa Stunting: Edukasi Gizi pada Ibu di Pedukuhan Magirejo, Ngalang, Gedangsari, Gunung Kidul - Handayani, Lina; Sutikno, Tole; Khasanah, Sovy Nur; Novianti, Tria Nisa (Cahaya Pengabdian, 2025)
Stunting is a chronic nutritional problem that affects children’s physical and cognitive growth. In Indonesia, the prevalence of stunting remains relatively high, although it has shown a declining trend. The contributing factors to stunting include parenting practices, nutritional intake, and food access. This community service program aims to improve the understanding of pregnant women, breastfeeding mothers, and young families about the importance of balanced nutrition, exclusive breastfeeding, and healthy complementary feeding (MP-ASI) as an effort to prevent stunting. Educational activities were conducted for 13 mothers of toddlers in Padukuhan Magirejo, using visual media, counseling sessions at the Posyandu, and leaflet distribution. Knowledge was measured through pretest and posttest questionnaires. The results indicated an increase in participants’ knowledge and commitment to better nutritional practices. Early intervention through this educational program is expected to contribute to reducing stunting cases.